Toms and dees : transgender identity and female same-sex relationships in Thailand - Sinnott, Megan (Southeast Asia--politics, meaning, memory., 2004)
A vibrant, growing, and highly visible set of female identities has emerged in Thailand known as tom and dee. A "tom" (from "tomboy") refers to a masculine woman who is sexually involved with a feminine partner, or "dee" (from "lady"). The patterning of female same-sex relationships into masculine and feminine pairs, coupled with the use of English derived terms to refer to them, is found throughout East and Southeast Asia. Have the forces of capitalism facilitated the dissemination of Western-style gay and lesbian identities throughout the developing world as some theories of transnationalism suggest? Is the emergence of toms and dees over the past twenty-five years a sign that this has occurred in Thailand? Megan Sinnott engages these issues by examining the local culture and historical context of female same-sex eroticism and female masculinity in Thailand. Drawing on a broad spectrum of anthropological literature, Sinnott situates Thai tom and dee subculture within the global trend of increasingly hybridized sexual and gender identities